2019
DOI: 10.1521/pedi_2017_31_327
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorder Features and Paraphilic Interests Among Undergraduates: Differential Relations and Potential Antecedents

Abstract: We examined the relations between: (1) narcissism, psychopathy, DSM-5 personality disorder symptom counts; and (2) paraphilic interests among undergraduates (N = 608). Base rates of paraphilic interests were appreciable. The disinhibition and meanness features of psychopathy and the entitlement and exploitativeness features of narcissism were robustly associated with paraphilic interests, particularly sexual sadism, whereas the boldness features of narcissism and psychopathy were essentially unrelated to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
3
14
0
1
Order By: Relevance
“…Of note, some prior studies have reported significant associations between higher levels of psychopathy and greater sexual interests for uncommitted, impersonal, and sadomasochistic or otherwise deviant elements (Baughman et al, 2014;Skovran et al, 2010;Visser et al, 2015;Watts et al, 2017b;Williams et al, 2009). Skovran et al (2010) found that sex offenders who met the diagnostic criteria for psychopathy (i.e., PCL-R scores !25) reported greater levels and a greater variety of deviant sexual fantasies compared to non-psychopathic sex offenders.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Of note, some prior studies have reported significant associations between higher levels of psychopathy and greater sexual interests for uncommitted, impersonal, and sadomasochistic or otherwise deviant elements (Baughman et al, 2014;Skovran et al, 2010;Visser et al, 2015;Watts et al, 2017b;Williams et al, 2009). Skovran et al (2010) found that sex offenders who met the diagnostic criteria for psychopathy (i.e., PCL-R scores !25) reported greater levels and a greater variety of deviant sexual fantasies compared to non-psychopathic sex offenders.…”
mentioning
confidence: 98%
“…Psychopathy; sexual deviance; sexual fantasies; gender differences; paraphilia Understanding sexual deviance has historically been a difficult endeavor, partly due to controversies in the very definition of sexual deviance (Bartels & Gannon, 2011;Laws & O'Donohue, 2008). These definitional issues have likely hampered the study of the etiology and correlates of sexual deviance, which is crucial to understand sexual deviance and to refine prevention and intervention programs (Watts, Nagel, Latzman, & Lilienfeld, 2017b). Overall, a common criterion for sexual deviance concerns the unusual nature of the source of arousal, either in terms of anomalous activity (e.g., voyeurism) or in terms of anomalous targets (e.g., pedophilia) (Feierman & Feierman, 2000;Leitenberg & Henning, 1995;Williams, Cooper, Howell, Yuille, & Paulhus, 2009).…”
mentioning
confidence: 99%
See 3 more Smart Citations